Browsing Personal Media archives with spatial context using panoramas - Adams, Brett; Greenhill, Stewart; Venkatesh, Svetha (ACM Press, 2006)
This paper presents novel techniques for using panoramas as spatial context to enhance browsing of personal media archives. This context, scenes where frequent media capture takes place, is present in the disparate photos and videos, but not leveraged by traditional browsing techniques (e.g. thumbnails or zoomable interfaces). Coarse geo-position is often an insufficient index at such media capture hotspots. We experiment with panoramic video, which presents archive video organically blended with panoramas of media capture hotspots; Immersive browsing and filtering with media items projected onto spherical panoramas; and Detection and representation of links between panoramas to enable browsing of situated media in quasi-3D. We present proof-of-concept implementations and observations of their effectiveness, limitations, and open problems. Experiments confirm the intuition that each holds promise for augmenting traditional browsing environments.